Neuroimmune axis in gastrointestinal cancers: From mechanisms to therapeutic breakthrough - Yixuan Zhang; Jintian Chen; Yiwei Zhou; Yanjun Jiang; Jielun Hu; Xiaodong Liu; Jingying Zhou (Cell Reports, 2025)
Summary: Accumulating evidence has demonstrated that tumor cells can co-opt the nervous and immune systems to facilitate their growth, progression, and metastasis. Tumor innervation has been reported to regulate cancer development either directly or indirectly by modulating immune evasion through the neuroimmune axis. Building on insights into the mechanisms of cancer-neuroimmune interactions, attention is turning to developing novel therapeutics by repurposing neuropsychiatric drugs or using neuromodulation. Given the rich innervation of the gastrointestinal (GI) tract and its accessory organs, we summarize the current understanding of neuroimmune networks in GI cancers, focusing on the most recent updates of neurotransmitter-receptor pathways and tumor-innervating nociceptors. Additionally, we discuss the underlying mechanisms of these pathways and explore their therapeutic implications, which may potentially lead to new approaches for combinatory immunotherapies in GI cancers.